Literary and Conceptual Analysis of Dwividhopakramaneeya Adhyaya of Ashtang Sangraha and Ashtang Hridaya - Aishwarya Ashish Joglekar; Mahesh Vyas; Meera K. Bhojani (Indian Journal of Ayurveda and Integrative Medicine KLEU)
Dwividhopakramaneeya Adhyaya is a specialty of Acharya Vagbhatt being a part of both the treatises Ashtang Hridaya and Ashtang Sangraha. It paves the way for the understanding of treatment protocol for any disease. In the present study, the analysis of the chapter considers the different technical, literary, and grammatical aspects that can help widen the knowledge base. The detailed analysis of a chapter can be useful in better understanding other chapters in the texts. The objective of this article is to analyze the Dwividhopakramaneeya Adhyaya mentioned in the A. H and A. S. texts in light of conceptual and critical domains. The analysis and discussion are done considering the domains of the grammatical aspects of chapter etymology, authorship, position, number of verses mentioned in both A. H. and A. S, type of Sutra, Chanda, Samaasa, Vibhakti in the Adhyaya, analysis of chapter based on the literary tools Tantrayukti (Arthashraya, Vyakhya, Tacchilya, Upama, Nyaya), technical Ayurveda terms (Ashtavidha Prashna, Dasha Prakarana, Adhyayana-Adhyapan-Tadvidya Sambhasha, Pada-Paada-Shloka, Vakyasha-Vakyarthasha-Artha-Avayavasha) along with navigating the different concepts mentioned in Adhyaya such as Trisutra, Pramana, and Siddhant. It can be concluded that Adhyaya is pivotal for understanding all the diseases and treatment modalities as per Ayurveda. The methodology adopted to analyze the Adhyaya can be beneficial to understand the different aspects of the text as a whole. The present article can aid in learning and understanding of other Adhyaya in Ayurveda texts thus opening future areas of research to establish and assess the fundamental principles of Ayurveda.